Binaural Pitch Fusion in Bilateral Cochlear Implant Users. Issue 2 (March 2018) - Reiss, Lina A. J.; Fowler, Jennifer R.; Hartling, Curtis L.; Oh, Yonghee
Abstract : Objectives: Binaural pitch fusion is the fusion of stimuli that evoke different pitches between the ears into a single auditory image. Individuals who use hearing aids or bimodal cochlear implants (CIs) experience abnormally broad binaural pitch fusion, such that sounds differing in pitch by as much as 3–4 octaves are fused across ears, leading to spectral averaging and speech perception interference. The goal of this study was to determine if adult bilateral CI users also experience broad binaural pitch fusion. Design: Stimuli were pulse trains delivered to individual electrodes. Fusion ranges were measured using simultaneous, dichotic presentation of reference and comparison stimuli in opposite ears, and varying the comparison stimulus to find the range that fused with the reference stimulus. Results: Bilateral CI listeners had binaural pitch fusion ranges varying from 0 to 12 mm (average 6.1 ± 3.9 mm), where 12 mm indicates fusion over all electrodes in the array. No significant correlations of fusion range were observed with any subject factors related to age, hearing loss history, or hearing device history, or with any electrode factors including interaural electrode pitch mismatch, pitch match bandwidth, or within-ear electrode discrimination abilities. Conclusions: Bilateral CI listeners have abnormally broad fusion, similar to hearing aid and bimodal CI listeners. This broad fusion may explain the variability of binaural benefits for speech perception in quiet and in noise in bilateral CI users. Abstract : Supplemental Digital Content is available in the text.